2012
DOI: 10.1007/s00246-012-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sildenafil on Echocardiographic Indices of Myocardial Performance After the Fontan Operation

Abstract: The objective of this study was describe the impact of sildenafil on echocardiographic measures of myocardial performance in children and young adults with a functional single-ventricle physiology late after Fontan surgery. A double-blind, placebo-controlled, crossover trial was conducted in children and young adults after the Fontan operation at a single pediatric center. Subjects were randomized to receive placebo or sildenafil (20 mg tid) for 6 weeks. After a 6-week washout period, subjects were crossed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 25 publications
3
75
0
Order By: Relevance
“…Extending this experience, Goldberg et al 9,10 demonstrated an improvement in ventilatory efficiency and ventricular performance after a 6-week period of sildenafil treatment.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 87%
See 2 more Smart Citations
“…Extending this experience, Goldberg et al 9,10 demonstrated an improvement in ventilatory efficiency and ventricular performance after a 6-week period of sildenafil treatment.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 87%
“…3,[8][9][10] This postsildenafil increase in CI may be attributed to a relative increase in HR, an unchanged EDVi, and a decrease in both TPRi and ESVi when compared with the presildenafil setting. TPRi was observed to be lower throughout exercise in the postsildenafil setting, but the most significant difference was observed during high-intensity exercise where TPRi remained unchanged, in contrast to the increase observed during exercise before sildenafil.…”
Section: Effect Of Sildenafil On Exercise Hemodynamicsmentioning
confidence: 95%
See 1 more Smart Citation
“…This highlights the importance of active hemodynamic management in the care of long-term survivors. Although some studies have reported the beneficial roles of some medications [e.g., administration of sildenafil (30), amrinone (78), or sodium nitroprusside (93)] in increasing resting CO or improving ventricular performance, to date, evidence supporting the longterm effectiveness of certain interventions in systemically improving hemodynamic conditions remains absent. The present theoretical study demonstrates that the mechanisms underlying the regulation of CO and central venous pressure differ significantly between the Fontan circulation and the biventricular circulation, which implies that some conventional medications for treating patients with biventricular physiology might not be applicable to Fontan patients.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose improved peak V ⋅ o 2 during exercise with a measurable increase in both pulmonary and systemic blood flow at peak exercise. 211,212 Others series showed a favorable impact on the Doppler-derived myocardial performance index 213 and systolic arterial and ventricular elastance. 214 With longer therapy, a double-blind, placebocontrolled crossover trial showed an improvement in the ventilatory efficiency slope during cardiopulmonary exercise testing, although other parameters were not improved.…”
Section: • Plastic Bronchitismentioning
confidence: 98%